The Effect of Climate Change on Important Climate Variables in Taiwan and Its Potential Impact on Crop Production - Shih-Lun Fang; Bing-Yun Tsai; Chun-Yi Wu; Sheng-Chih Chang; Yi-Lung Chang; Bo-Jein Kuo (Agriculture)
Alterations in reference evapotranspiration (ET0) and precipitation (PP) resulting from global warming substantially affect water resources and agriculture. This study analyzed trends in ET0, PP, and key climate variables—including air temperature (T), vapor pressure deficit (VPD), wind speed, and solar radiation (Rs)—across Taiwan from 1995 to 2022. Trends were assessed using the modified Mann–Kendall test and the multivariate Man–Kendall test at both station-wise and multi-station scales. Results indicated that ET0 was primarily influenced by Rs, followed by T, wind speed, and VPD. Station-wise analysis revealed increasing trends in annual and seasonal T, Rs, and ET0, while over 50% of wind speed series showed significant declines. Multi-station analysis confirmed an overall rise in ET0. In eastern Taiwan, rising T and declining VPD and wind speed may increase the risk of pest and disease outbreaks. The arid index exhibited a general downward trend, particularly in summer, with 75% of the stations in eastern Taiwan exhibiting significant declines, suggesting a shift toward drier conditions. These findings imply that fewer crop options may be suitable for cultivation in eastern Taiwan due to water resource constraints. Additionally, seasonal and annual PP showed slight decreases, with a more uneven distribution observed in central Taiwan. Therefore, improving hydraulic facilities and irrigation systems will become important. Furthermore, comparisons between the multivariate Mann–Kendall test and the traditional univariate approach revealed some different results, indicating the need for further research to identify a more reliable approach.